Integritas Informasi Keuangan dan Nilai Pasar Perusahaan - Suhariyanto, Suhariyanto; Sumaryo, Sumaryo (Penerbit Goodwood, 2025)
Purpose: This study aims to provide empirical evidence and examine the role of Integrity of Financial Information (IFI), Mining Corporate Governance (MCG), and Audit Quality (AQU) on Corporate Market Value (CMV). Methodology/approach: Based on stakeholder theory, the authors developed and tested hypotheses using secondary data from 120 observations of the Indonesian mining sector from 2019 to 2023. The sample method employed was purposive sampling, and the analysis was conducted using panel data with EViews 13. Results/findings: The results show that Integrity of Financial Information (IFI) has a positive effect on Corporate Market Value (CMV), Mining Corporate Governance (MCG) has a positive effect on Corporate Market Value (CMV), and Audit Quality (AQU) has a positive effect on Corporate Market Value (CMV) in mining companies listed on the IDX during 2019–2023. Conclusions: Companies with high Integrity of Financial Information (IFI), strong Mining Corporate Governance (MCG), and high Audit Quality (AQU) are more likely to increase their Corporate Market Value (CMV) in the context of the Indonesian mining industry. Limitations: The use of MCG proxies with an index of the proportion of independent commissioners, board of directors, and audit committees resulted in a coefficient of determination of only 30.45%. Contribution: This study provides a new approach by applying stakeholder theory to examine the effect of Integrity of Financial Information on Corporate Market Value (CMV) in Indonesian mining companies.